2011
DOI: 10.1007/s10853-011-5310-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibre fabrication in a temperature and humidity controlled environment for improved fibre consistency

Abstract: Fabricating nanofibres with reproducible characteristics is an important demand in the membrane industry in order to establish commercial viability. In this study, the effect of controlled atmospheric conditions on electrospun cellulose acetate (CA) nanofibres was evaluated for temperatures ranging 17.5-32.5°C and relative humidity ranging 20-70%. CA solution (0.2 g/mL) in a solvent mixture of acetone/dimethylformamide/ethanol (2:2:1) was electrospun into nonwoven fibre mesh with the fibre diameter ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 33 publications
2
66
0
Order By: Relevance
“…The effects of humidity on fiber morphology are poorly understood and/or there are contradictory effects that have been observed that appear to be dependent on properties such as the type of polymer, polymer-solvent combination, molecular weight, polymer hydrophilicity, and size of the electrospun structure. [62][63][64][65][66] Both the incomplete reporting of electrospinning conditions and the limited understanding of environmental effects on fiber formation make it difficult to predict and reproduce electrospun scaffold microarchitecture.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of humidity on fiber morphology are poorly understood and/or there are contradictory effects that have been observed that appear to be dependent on properties such as the type of polymer, polymer-solvent combination, molecular weight, polymer hydrophilicity, and size of the electrospun structure. [62][63][64][65][66] Both the incomplete reporting of electrospinning conditions and the limited understanding of environmental effects on fiber formation make it difficult to predict and reproduce electrospun scaffold microarchitecture.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst atmospheric conditions are known to contribute to fibre diameter and morphology, unless these conditions vary significantly from standard atmospheric conditions, the effects are minimal [32,50,60]. Additionally these parameters are often not quoted in the literature and are difficult to control with most laboratory setups.…”
Section: Experimental Parametersmentioning
confidence: 99%
“…As discussed in Chapter 2, these environmental factors cannot be controlled in the current electrospinning setup; they are only monitored and recorded at the beginning of each spin. It has been shown in other studies that temperature and humidity affect the electrospinning process 64,65,81 . The environmental fluctuations therefore may have contributed to variability in fiber diameter.…”
Section: Challenges and Limitationsmentioning
confidence: 91%
“…Finally, environmental effects could have an impact on cone stability and subsequent variability of the scaffolds, as demonstrated in the literature 64,65,68,81 . An additional analysis that was performed with the preliminary data from this thesis also suggested that environment had an impact on fiber diameter.…”
Section: Taylor Cone Stabilitymentioning
confidence: 95%
See 1 more Smart Citation